A Text Analysis on Joko Widodo’s Speech Text on Indonesia Independence Day - Asep Anwar Siddiq; Didin Nuruddin Hidayat; Alek Alek; Adrefiza Adrefiza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to describe the President's speech text as a critical discourse analysis taken on the Indonesian Republic Secretariat Cabinet website, conveyed by Ir. Joko Widodo as the 7th president of the Republic of Indonesia. The methodology used by the researchers was a descriptive qualitative method. This textual content analysis is base on Van Dijk's design by which the research unit section is divide into three parts: macro-structure, supra structure and microstructure. The study revealed that the textual content was analyzed thematically or the discourse's subject in the macro-structure. The theme of Jokowi's speech was about Indonesia's excellence. It can be seen clearly from almost all the paragraphs in the statement stating one general subject, namely, about Indonesia's superiority. Then, for the supra-structure, Jokowi's speech text is divided into three main elements: opening, content, and closing, which consisted of two opening paragraphs, eighteen content paragraphs, and two closing paragraphs. The last was microstructure. It was analyzed in a semantic way, which refers to the text's social meaning and the language modes used in the text. Semantically, the text of Jokowi's speech was analyzed from its setting, detail, intention, and presupposition. From Jokowi's information, this expression shows that the speech's overall form contained all the speeches delivered by him; opening, filling, and closing. What has become very clear to set Jokowi apart from many other international public figures is that he uses simple language. The things that Jokowi has brought can be an excellent lesson for people when speaking in front of the audience. Keywords: Critical Discourse Analysis, Jokowi’s Speech Text, Van Dijk’s Design